Pelaksanaan Kurikulum Tingkat Satuan Pendidikan Di Madrasah Tsanawiyah Negeri 9 Kampar - Asrianto, Surnadi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This study aims to determine the implementation of the education unit level curriculum at MTsN 9 Kampar, Tambang District, Kampar Regency. This research is a field research that is qualitative analysis. This research also uses descriptive data, because the research is done by interpreting, describing the data, classifying the form of the data, then proceeding with interpretation and finally extrapolating, which concerns the meaning and results of the research achieved as a contribution of thought. Based on the results of the study, it showed that the implementation of KTSP at Madrasah Tsanawiyah Negeri 9 Kampar still encountered problems including the teacher not making learning module programs for students, not using media and varied learning resources, weak class management in the learning process and still traditional learning models at Madrasah Tsanawiyah Negeri 9 Kampar are the following symptoms: Not making learning module programs for students, Not using varied learning media and sources, Weak classroom management in the learning process and Still traditional learning models